Interactive effects of culture and sex hormones on the sex role self-concept - Pletzer, Belinda; Petasis, Ourania; Ortner, Tuulia; Cahill, Larry (Frontiers in Neuroscience, 2015)
Sex role orientation, i.e., a person's masculinity or femininity, influences cognitive and emotional performance, like biological sex. While it is now widely accepted that sex differences are modulated by the hormonal status of female participants (menstrual cycle, hormonal contraceptive use), the question, whether hormonal status and sex hormones also modulate participants sex role orientation has hardly been addressed previously. The present study assessed sex role orientation and hormonal status as well as sex hormone levels in three samples of participants from two different cultures (Northern American, Middle European). Menstrual cycle phase did not affect participant's masculinity or femininity, but had a significant impact on reference group. While women in their follicular phase (low levels of female sex hormones) determined their masculinity and femininity in reference to men, women in their luteal phase (high levels of female sex hormones) determined their masculinity and femininity in reference to women. Hormonal contraceptive users rated themselves as significantly more feminine and less masculine than naturally cycling women. Furthermore, the impact of biological sex on the factorial structure of sex role orientation as well as the relationship of estrogen to masculinity/femininity was modulated by culture. We conclude that culture and sex hormones interactively affect sex role orientation and hormonal status of participants should be controlled for when assessing masculinity and/or femininity.